2016
DOI: 10.1016/j.cmet.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

ERRγ Is Required for the Metabolic Maturation of Therapeutically Functional Glucose-Responsive β Cells

Abstract: SUMMARY Pancreatic β cells undergo postnatal maturation to achieve maximal glucose-responsive insulin secretion, an energy intensive process. We identify estrogen-related receptor γ (ERRγ) expression as a hallmark of adult, but not neonatal β cells. Postnatal induction of ERRγ drives a transcriptional network activating mitochondrial oxidative phosphorylation, the electron transport chain, and ATP production needed to drive glucose-responsive insulin secretion. Mice deficient in β cell-specific ERRγ expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
180
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(184 citation statements)
references
References 48 publications
(61 reference statements)
3
180
1
Order By: Relevance
“…Our finding that mitochondrial gene expression decreases during beta-cell maturation appears, at first, to contradict a recent study reporting mRNA increases of oxidative phosphorylation and respiratory chain components when bulk islet samples of two- and six-week-old mice were compared (Yoshihara et al, 2016). The discrepancy could be explained by the different time window studied by Yoshihara and colleagues.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding that mitochondrial gene expression decreases during beta-cell maturation appears, at first, to contradict a recent study reporting mRNA increases of oxidative phosphorylation and respiratory chain components when bulk islet samples of two- and six-week-old mice were compared (Yoshihara et al, 2016). The discrepancy could be explained by the different time window studied by Yoshihara and colleagues.…”
Section: Discussioncontrasting
confidence: 99%
“…2D; S2B). Thus, we propose that the here-identified subpopulation of beta-cells with high mitochondrial membrane potential represents a rare immature population with high proliferative capacity, whereas beta-cells that upregulate oxidative phosphorylation genes later postnatally represent cells with a mature insulin secretory response (Yoshihara et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In muscle, ERR isoforms variously contribute to aspects of mitochondrial biogenesis, mitochondrial maintenance, vascularity, energy expenditure, and mitochondrial uncoupling. Although the activity of ERRα is dependent on PGC1α/β induction, ERRγ is sufficient to orchestrate oxidative functions in highly energetic tissues such as type 1 muscle fibers and pancreatic beta cells (Pei et al, 2015; Narkar et al, 2011; Dufour et al, 2007; Kida et al, 2015; Wang et al, 2015; Alaynick et al, 2007, 2010, Yoshihara et al, 2016). In muscle, ERRγ functions to maintain a highly oxidative basal state even in the absence of exercise, and transgenic expression is sufficient to promote type 1 fiber-type switching (Narkar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In muscle, ERRγ functions to maintain a highly oxidative basal state even in the absence of exercise, and transgenic expression is sufficient to promote type 1 fiber-type switching (Narkar et al, 2011). In the pancreas, ERRγ is required for beta cell maturation and glucose-stimulated insulin secretion (GSIS), and its loss, by targeted knockout, leads to glucose intolerance (Yoshihara et al, 2016). Although ERRγ is also highly expressed in BAT, its contribution to BAT identity or function is not known.…”
Section: Introductionmentioning
confidence: 99%
“…130133 Essrg -deficient mice die soon after birth, due to the critical need for their myocardium to switch from glycolysis to FA oxidation. 134 More recent studies have shown that ERRγ orchestrates the transcriptional program that activates glucose OXPHOS and ATP production essential for the function of pancreatic β cells 135 and neurons. 136 These results strongly suggest that ERRγ also has a role in regulating T-cell function by controlling mitochondrial metabolism, a hypothesis that we are in the process of testing.…”
Section: Cd4+ T Cells In Slementioning
confidence: 99%